2016
DOI: 10.1007/s10286-016-0362-x
|View full text |Cite
|
Sign up to set email alerts
|

The pathophysiologic mechanisms associated with hypotensive susceptibility

Abstract: Introduction Patients with vasovagal syncope (VVS) and positive tilt table test (TTT) were not found to benefit from pacing in the ISSUE-3 trial despite the presence of spontaneous asystole during monitoring. "Hypotensive susceptibility" unmasked by TTT was reported as a possible explanation. The purpose of this study was to assess the pathophysiologic mechanisms associated with hypotensive susceptibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Similarly, Jardine et al reported that HR increased to a greater extent in patients who went on to faint than in controls. On the other hand, Chaddha et al found that HRs were lower during HUT in patients who went on to have a positive test than in tilt‐negative subjects. In any case, while the HR differences in the above reports remain to be resolved, the studies did not attempt to ascertain whether “within group” HR differences resulted in demonstrable differences in VVS susceptibility.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, Jardine et al reported that HR increased to a greater extent in patients who went on to faint than in controls. On the other hand, Chaddha et al found that HRs were lower during HUT in patients who went on to have a positive test than in tilt‐negative subjects. In any case, while the HR differences in the above reports remain to be resolved, the studies did not attempt to ascertain whether “within group” HR differences resulted in demonstrable differences in VVS susceptibility.…”
Section: Discussionmentioning
confidence: 98%
“…Its study is more exhaustive and requires a good anamnesis, knowing the drugs used by the patient, knowing the concomitant diseases and careful monitoring to get closer to the diagnosis. We observe the high frequency of orthostatic hypotension as a cause for syncope, which is attributable in many cases to advanced age, failure of baroreflexes, cardiovascular and neurological diseases, and polypharmacy [29] [66] [67].…”
Section: In Summentioning
confidence: 99%
“…A further confounding diagnostic challenge is that patients with POTS and their families report ongoing difficulties related to diagnosis, medical stigma, and the challenges related to “living with an invisible illness.”33 They are often told their symptoms are purely psychosomatic in nature or due to anxiety 34,35. It is common for youth with POTS to meet with as many as seven doctors before being diagnosed and to continue to see numerous specialists to determine a treatment plan after diagnosis 6. Once a POTS specialist has been identified, the wait to be seen is estimated to be between six to 36 months, further delaying accurate diagnosis and treatment, with youth experiencing an average of 5 years to diagnosis after symptom presentation 33…”
Section: Challenge I: Complexities and Misunderstandingsmentioning
confidence: 99%
“…At least one-third of patients develop POTS symptoms prior to age 18 with a median age of symptom onset at 13.1 years of age 5,6. Youth with POTS are typically female (5:1), Caucasian, and diagnosed between the ages of 12–40 with over 50% reporting additional somatic symptoms including chronic fatigue, nausea, and sleep difficulties 5,79.…”
Section: Introductionmentioning
confidence: 99%